A Comparison of Strategies to Improve Uptake of COVID-19 Vaccine among High-Risk Adults in Nairobi, Kenya in 2022 - Joan Yego; Robert Korom; Emma Eriksson; Sharon Njavika; Oulimata Sane; Purity Kanorio; Oliver Rotich; Stellah Wambui; Eunice Mureithi (Vaccines, 2023)
Background: COVID-19 vaccine uptake in Kenya is still low compared to other countries, especially in Europe and North America. In most parts of the country, a large percentage of the Kenyan population remains unvaccinated. As of October 2022, the Ministry of Health (Kenya) estimates that only 36.2% of the adult population had been fully vaccinated. Methods: We conducted an experimental study in April 2022 targeting unvaccinated adults who had a history of hypertension and/or diabetes and those in the 60+ age group. We tested various messaging approaches using two different intervention channels. Results: Although the overall rate of vaccinated individuals according to national records is low, responses from the study group collected through phone call conversations show that higher-risk adults such as those older than 60 or those with chronic illnesses have a remarkably high vaccination rate of 89%. After the study, four participants received a COVID-19 vaccine within 1 month of the intervention. These four participants all received a loss-messaging intervention approach during the study. Conclusion: This study supports a national approach to increasing COVID-19 vaccination rates using loss-messaging directed at unvaccinated, high-risk individuals.